A rhetorical analysis of SABC3's flagship Bulletin : In what ways does the SABC succeed and/or fail in persuading viewers that its version of the news is credible? - Nkoala, Sisanda (Centre for Film and Media Studies, 2016)
This dissertation sets out to add to the existing body of research on the SABC by performing a rhetorical analysis of SABC 3's flagship English news bulletin, broadcast between 18:30 and 19:30, weekdays, and 19:00 and 19:30 on weekends. The purpose of this analysis is to determine the manner in which the SABC attempts to position itself as a credible news source through its use of the rhetorical tools of persuasion. As texts presented to an audience with the intention of persuading them of certain ideas, it is possible to study and analyse television news reports by employing the same rhetorical analysis techniques that one would use when analysing a political speech or any other rhetorical text. This dissertation is broken up into two major sections. Part one will discuss the theories and research around the notion of television news as rhetorical texts, setting the stage for part two of the dissertation, which will actually perform a rhetorical analysis on selected news stories aired on SABC 3 over a period of 30 days. The key conclusions from this research are that the SABC frequently employs the pathos proof in its reports, primarily through the reporters using emotive language in their scripts, even though this is not always accompanied by corresponding footage. Instead of relying primarily on reporters to state and interpret the emotional aspects of the story, the broadcaster should be using its visuals to do this, drawing on the television journalism principle of 'show, don't tell', where visuals are the primary means through which a story is told, not the words. What the broadcaster should instead be doing is using the logos proof more, to make sound arguments for some of the claims that are made in its reports. The second key conclusion is that the broadcaster relies on the epideictic genre of rhetoric in most of its reports, when the deliberative and judicial genres would be more fitting. The SABC has lost a significant number of viewers from the days when it was the sole television news broadcaster in South Africa, and there were no other alternatives. This dissertation shows that one of the main reasons for this is that the public broadcaster is failing to produce its news reports in a manner that correctly employs the tools of rhetoric to persuade viewers that its version of the news is credible.